2009
DOI: 10.1007/s00464-009-0745-3
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic resection for hepatocellular carcinoma: a matched-pair comparative study

Abstract: Laparoscopic resection of HCC for selected patients gave a better postoperative outcome without oncologic consequences. Prospective trials are required to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
163
3
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(190 citation statements)
references
References 31 publications
15
163
3
7
Order By: Relevance
“…The safety and feasibility of the laparoscopic approach and its short-term benefits for HCC patients with chronic liver dysfunction have been demonstrated by several series [21][22][23][24][25][26][27][28][29][30][31] . To date, several studies have investigated the major differences between laparoscopic hepatectomy and open hepatectomy (Tables 1 and 2) [32][33][34][35][36][37][38][39] . Favorable short-term results, including fewer incidences of ascites and liver failure, and shorter postoperative hospital stays, correlate with the laparoscopic procedure.…”
Section: Laparoscopic Hepatectomy For Hcc Patients: An Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The safety and feasibility of the laparoscopic approach and its short-term benefits for HCC patients with chronic liver dysfunction have been demonstrated by several series [21][22][23][24][25][26][27][28][29][30][31] . To date, several studies have investigated the major differences between laparoscopic hepatectomy and open hepatectomy (Tables 1 and 2) [32][33][34][35][36][37][38][39] . Favorable short-term results, including fewer incidences of ascites and liver failure, and shorter postoperative hospital stays, correlate with the laparoscopic procedure.…”
Section: Laparoscopic Hepatectomy For Hcc Patients: An Overviewmentioning
confidence: 99%
“…Favorable short-term results, including fewer incidences of ascites and liver failure, and shorter postoperative hospital stays, correlate with the laparoscopic procedure. Tranchart et al [36] reported laparoscopic resection of HCC for selected patients resulted in better postoperative outcomes without long-and short-term oncologic consequences (42 each laparoscopic-and open-hepatectomy patients, with more than 96% Child-Pugh class A patients and mostly anatomical resection). Early postoperative recovery and discharge with less postoperative pain are usual advantages of laparoscopic surgery.…”
Section: Laparoscopic Hepatectomy For Hcc Patients: An Overviewmentioning
confidence: 99%
“…However, in selected patients who undergo surgery by experienced hands, one of the most important advantage of the laparoscopic approach is the potential improvement in terms of blood loss and transfusion rates [4][5][6][7][8][9][10][11]. This specific improvement of the laparoscopic approach in comparison to open surgery was particularly underlined by the experts at the Morioka consensus.…”
Section: Discussionmentioning
confidence: 99%
“…), bleeding control during laparoscopic liver resection (LLR) is a liverspecific improvement, which has been underlined by many experts [4][5][6][7][8][9][10][11]. Several studies aimed to elucidate the factors responsible for reduced blood loss during laparoscopic liver surgery.…”
Section: Introductionmentioning
confidence: 99%
“…During the parenchymal transection phase, central venous pressure is lowered to between 2 and 4 mmHg with the use of nitrates, nitrous oxide, and dieresis. Combined with the tamponade effect of pneumoperitoneum, this technique minimizes blood loss from venous parenchymal bleeding (Tranchart, H et al 2010). Concern has been raised over the possibility of carbon dioxide embolism during laparoscopic liver surgery; however, extensive use of CO2 as an intravenous contrast agent in interventional radiology procedures shows that these fears are probably overstated (Hawkins, IF & Caridi, JG 1998).…”
Section: Anesthesia and Intraoperative Carementioning
confidence: 99%